2006
DOI: 10.1177/205873920601900121
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus DNA, P53 and KI67 Expression in Penile Carcinomas

Abstract: Our study is aimed at evaluating the presence of p53 and Ki67 expression by immunohistochemistry in a series of 11 paraffin-embedded penile carcinomas. We also investigated the presence of Human Papillomavirus (HPV) DNA in these tumours and performed an accurate typing by DNA sequencing on positive samples. Immunohistochemistry (IHC) was performed with the anti-p53 and Ki67 mouse monoclonal antibodies. DNA extracted from small sections of each specimen was submitted to amplification with HPV specific general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…ILD was indicated by the presence of abnormal pulmonary mesenchyma, nodules, hypertrophy, and fibrosis. COPD was characterized by partial or complete pulmonary emphysema with clinical symptoms including shortness of breath, chest tightness, fever, and hemoptysis (Joshi et al, 2005;Gentile et al, 2006;Battaglia et al, 2006;Wohlfert and Belkaid, 2010).…”
Section: Clinical Datamentioning
confidence: 99%
“…ILD was indicated by the presence of abnormal pulmonary mesenchyma, nodules, hypertrophy, and fibrosis. COPD was characterized by partial or complete pulmonary emphysema with clinical symptoms including shortness of breath, chest tightness, fever, and hemoptysis (Joshi et al, 2005;Gentile et al, 2006;Battaglia et al, 2006;Wohlfert and Belkaid, 2010).…”
Section: Clinical Datamentioning
confidence: 99%
“…In a large case series, HPV DNA was positive in invasive penile cancer in 40% to 50% of cases. Thus, many studies have shown a strong correlation of the presence of HPV types 16 and 18 with penile carcinoma (Daling et al, 2005;Gentile et al, 2006;Pascual et al, 2007;Senba et al, 2006;Tornesello et al, 2008;Villa & Lopes., 1986).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…In a large case series, HPV DNA was positive in invasive penile cancer in 40% to 50% of cases. Thus, many studies have shown a strong correlation of the presence of HPV types 16 and 18 with penile carcinoma Gentile et al, 2006;Pascual et al, 2007;Senba et al, 2006;Tornesello et al, 2008;Villa & Lopes., 1986). …”
Section: Effect On the Sperm Parametersmentioning
confidence: 99%